AB0182 Alternatively Activated Dendritic Cells Derived from Systemic Lupus Erythematosus Patients Have Tolerogenic Phenotype and Function. (9th June 2015) - Wu, H.J.; Lo, Y.; Luk, D.; Lau, C.S.; Mok, M.Y.
Abstract : Background: Generation of tolerogenic dendritic cells (DCs) has been extensively studied using cytokine, growth factor, genetic engineering and pharmacological methods. Tolerogenic DCs are increasingly explored as cell-based therapy in murine model of autoimmune diseases and may have potential therapeutic implications in the treatment of systemic lupus erythematosus (SLE) that is characterised by dysregulated innate and adaptive immune responses. Objectives: In this study, we generated alternatively activated DCs (aaDCs) from SLE patients and healthy subjects and examined their immunoregulatory properties in vitro . Methods: aaDCs were generated by treating monocyte-derived DCs by combination of 1, 25 dihydroxyvitamin D(3) (vitD3) and dexamethasone followed by lipopolysaccharide-induced maturation Results: Lupus aaDCs were found to acquire semi-mature phenotype that remained resistant to immunostimulatory effect of sCD40L, CpG-DNA and SLE serum. These cells produced low level of IL-12 but high level of IL-10. They had attenuated allostimulatory effect on T cell activation and proliferation comparable to normal aaDCs and demonstrated differential immunomodulatory effects on naïve and memory T cells. These aaDCs were capable of inducing IL-10 producing regulatory T effectors from naïve T cells whereas they modulated cytokine profile with suppressed production of IFN-γ and IL-17 by co-cultured memory T cells with attenuated proliferation. The tolerogenicity of aaDCs was shown to be superior than those generated using vitD3 alone in lupus patients. aaDCs expressed lower level of RelB but apoptosis of DCs and IL12/IL-10 imbalance were not found to account for their tolerogenicity. Conclusions: Our data suggested that combination of vitD3 and dexamethasone represented a feasible method in the generation of tolerogenic DCs from SLE patients. Disclosure of Interest: None declared